Analytic interpolation and the degree constraint - Georgiou, Tryphon T. (Zielona Góra: Uniwersytet Zielonogórski)
Analytic interpolation problems arise quite naturally in a variety of engineering applications. This is due to the fact that analyticity of a (transfer) function relates to the stability of a corresponding dynamical system, while positive realness and contractiveness relate to passivity.
Keywords: analytic interpolation; uniformly optimal control; spectral analysis of time-series